Impact of Board Characteristics on Performance of Nepalese Commercial Banks - Patali, Chakra Bahadur (KVM Research Journal, 2025)
This study examines the board characteristics affects on Nepalese commercial banks performance. The dependent variables are return on equity and return on assets, while the independent variables are total assets, board size, bank age, founder directors, CEO age, and independent directors. The secondary data used in this study came from 17 commercial banks and included 85 observations from 2019–20 to 2023–2024. The information was gathered from Nepal Rastra Bank’s Banking and Financial Statistics as well as the annual reports of a few chosen commercial banks. The significance and importance of board characteristics and firm performance in Nepalese commercial banks are tested using estimated regression models. The results indicate a negative correlation between return on assets and board size. It suggests that a larger board would result in a lower return on assets. On the other hand, return on assets and CEO age are positively correlated. It demonstrates that a higher return on assets is correlated with an older CEO. Similarly, there is a negative correlation between return on assets and founder and independent directors. It demonstrates that the return on assets would decrease with the number of independent directors and founder directors. In a similar vein, the return on assets has a positive relationship with total assets and bank age. It suggests that a rise in total assets and bank age results in a rise in return on assets. However, board size is adversely correlated with return on equity. It suggests that a larger board would result in a lower return on equity. In a similar vein, return on equity and CEO age are positively correlated. It demonstrates that the return on equity would increase with the age of the CEO. Additionally, the regression results indicate that the beta coefficients for total assets and CEO age are positive. At the 5 percent level, the coefficients are significant only for independent directors and board size.